Determinants of oral health status: an ecological study in Iran - Bahareh Tahani; Alireza Akbarzadeh Baghban; Ali Kazemian (BMC Oral Health, 2023)
Abstract Objectives The aim of this ecological study was to assess the association between behavioral, social position, circumstance factors, and caries experience in 35- to 44-year-old adults in Iran at a provincial level. Materials and methods The data from the 2011 Iranian Oral Health Survey were obtained from all 31 provinces across Iran on the population level. Oral health status was measured as the number of decayed, missing (MT), and filled (FT) teeth and the percentage of the population who were edentulous. Data were also gathered from each province on the percentage of smokers (Non-Communicable Diseases Risk Factors Surveillance Provincial Report 2009), per capita consumption of free sugars, concentration of fluoride in the drinking water (National and Sub-national Burden of Disease (NASBOD) Survey), number of dentists per 10,000 people, mean years of schooling of adults, expected years of schooling of children, life expectancy at birth and Gross National Income (Integrated Public Use Microdata Series, Global Data Lab). The data were analyzed using simple and multiple linear regression (α = 0.05). Results Mean DMFT was positively associated with the percentage of smokers (B = 0.01 95%CI 0.01–0.14), and negatively with fluoride concentration (B =-2.6 95%CI -4.3- -0.96). The edentulousness percentage was positively associated with smoking (B = 0.2 (with 95%CI: 0.07–0.37) and negatively with mean years of education (B =-1.08 (with 95%CI: -2.04- -0.12). DT was associated with expected years of schooling (B =-0.6 (with 95%CI: -1.07- -0.17), negatively. Mt was negatively associated with life expectancy (B =-0.5 (with 95%CI: -1.1- -0.007), fluoride concentration (B =-3.4 (with 95%CI: -4.5- -1.5) and number of dentists per 10,000 people (B =-0.4 (with 95%CI: -0.8- -0.01). Mean Years of Schooling (B = 0.5 (with 95%CI: 0.2–0.8) and number of dentists per 10,000 people (B =-0.62 (with 95%CI: 0.51 − 0.48) were positively in associated with FT. Conclusions The present findings indicate that there were differences in the oral health measures and their social determinants among the provinces of Iran. Regarding the limitations of the study especially the limitation of the number of independent variables, it seems, this discrepancy could be better explained by social variables of the provinces such as income than by environmental factors.